Plan estratégico para el desarrollo de productos que permita preparar a las personas en situación de calle y facilite su re inserción socio-laboral. - Ortiz-Portuguez, Paula (Instituto Tecnológico de Costa Rica, 2016)
Indigence, or rather the street situation is a social problem that has been increasing from 2014 in Costa Rica. Historically social care of this problem has been characterized as initiatives from individuals, churches, ORG and others, who generally offer aid covering only basic needs (food, clothing, etc.). There are also aid to overcome drug addiction, however a large number of exceedances, presents relapse. One of the main causes of this, is the difficulty of socio-occupationally reintegration into society. In Costa Rica, there are few places that offer this type of preparation and help, but there is only one in the city of Cartago, El Centro de Atención Integral (Integral Care Center), which is not yet in operation, and neither considered the possibility of providing job readiness. This project presents a strategy that aims to facilitate the training of people homeless, with an agricultural focus, through the development of products following an idea of social design. Specifically, with the El Centro de Atención Integral of Cartago as context and under the concept of integration and selfsustainability the implementation of 4 workshops for a learning period between 4 to 6 months are proposed.
Proyecto de Graduación (Licenciatura en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Diseño Industrial, 2016.
Keywords: Integración; Motivación; Preparación; Agrícola; Autosustentable; Diseño de producto